Blue Eyes Syndrome Cases in the Duck Farms in the Village Modopuro, Mojosari, District Mojokerto, East Java - Albiruni Haryo (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2015)
Modopuro village in Mojokerto, East Java is a region where people are mostly producing local breeds of ducks that is well known called as a Mojosari duck. The Modopuro village located in a lowland area where their people have been farming the Mojosari local ducks for years. It was reported that the outbreaks of the Mojosari ducks occurred during the years of 2012 and 2013. The ducks died suddently with the clinical signs, such as discoloration of the eyes (blue eyes syndrome) within 3 days, torticolis, stumbling, and they were then dead.From the many anxiety of farmers will be the disease, it is necessary to identify the causes of disease and determination of disease prevention measures. Inspection carried out by bringing the infected ducks to Laboratoritum Pathology Faculty of Veterinary Medicine, Airlangga University to do a necropsy, histopathological examination, and HA - HI examination have done in Virology Laboratory of Veterinary Medicine, Airlangga University. Histopathological examination showed the presence of lesions in organs eyes, lungs, heart, and ceca tonsil. Further, HA-HI test indicates that 90% possibility of of disease blue eyes syndromeon duck farms in the village Modopuro in the second trimester of 2013, caused by the H5N1 virus.